Religious Theoryan Implications in Classroom Teaching (Sotang, Yearly Peer Reviewed Journal, 2019)
Religion is an elusive phenomenon, with agreed definitions hard to find. A theory of religion as a cultural artefact with historical significance that lies beyond historical facticity or the lack of it. An individual or group’s religion connotes above all a belief system that constitutes an option among a myriad of options, rather than a single inherent truth based on historical fact. While challenging to institutional religion and its many adherents, it is contended that such an appreciation of religion is not necessarily a threat to either but in fact has potential to be a source of enrichment to both, as well as to religion’s enhancement of global harmony. It is when such an appreciation is not present that an exclusivist ‘trigger’, lying hidden in any religion, can be released and become the cause of immeasurable conflict. Since respect for human life and dignity is fundamental to all religious tradition, it follows that respect for the freedom of through and expression must likewise be recognized as a fundamental principle of religions. The defense of civil liberties is a religious as well as a civic obligation. There are many conflict is growing up due to diversity of religious theory. Religious principle compels to obey involuntary work individual, collective and society too. Many people are depriving from education, humankind because of racism. World are conflict due to religious proudness. Indigenous people all over the world are in discrimination due to religious classify. Religious theory is not valuable every time. Religious theory must flexible where same religious can adjust. Religious theory should be correction if necessary. Different religious people should respect each other.